2019
DOI: 10.1007/978-3-030-29390-1_9
|View full text |Cite
|
Sign up to set email alerts
|

User Experience of Driver State Visualizations: A Look at Demographics and Personalities

Abstract: Driver state detection is an emerging topic for automotive user interfaces. Motivated by the trend of self-tracking, one crucial question within this field is how or whether detected states should be displayed. In this work we investigate the impact of demographics and personality traits on the user experience of driver state visualizations. 328 participants experienced three concepts visualizing their current state in a publicly installed driving simulator. Driver age, experience, and personality traits were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…The idea to display the detected driver states within a graphical UI has been evaluated in recent studies, e.g., by Völkel et al [42], within the AwareCar project at MIT [23], and in our own research [43]. Such a display can keep drivers informed regarding their current capacities and support in-vehicle systems to improve driver performance and safety [23].…”
Section: Driver State Displaymentioning
confidence: 99%
See 1 more Smart Citation
“…The idea to display the detected driver states within a graphical UI has been evaluated in recent studies, e.g., by Völkel et al [42], within the AwareCar project at MIT [23], and in our own research [43]. Such a display can keep drivers informed regarding their current capacities and support in-vehicle systems to improve driver performance and safety [23].…”
Section: Driver State Displaymentioning
confidence: 99%
“…Such a display can keep drivers informed regarding their current capacities and support in-vehicle systems to improve driver performance and safety [23]. Drivers generally seem open towards continuous driver state displays, provided the criticality of the situation is easily discernible [42,43]. If such a system incorporates notifications, the timing needs to be adaptive to the level of receptiveness and the driver's attentional states [44].…”
Section: Driver State Displaymentioning
confidence: 99%
“…With technical advancements, more and more elaborate emotionally sentient digital assistants will become feasible [32]. Other applications of affective in-car UIs have been realized by giving direct feedback to the driver regarding their current state, so they can reflect and adapt if necessary [4,44]; by actively influencing the driver, e.g., through music playback [13], and, more subliminally, through ambient lighting [16]; or by enhancing the driving experience in an emotional way, e.g., with emotional interaction in a feedback channel among nearby cars [45]. Coughlin et al envision an aware car which detects the driver's state from psycho-physiological data and influences them to stay in an optimum driving state [10].…”
Section: Affective Automotive User Interfacesmentioning
confidence: 99%
“…Use cases in this cluster are designed to improve the transparency of the emotion detection system. Inspired by related work [4,44], Driver State Display and Passenger State Display show the detected states of the driver / all occupants as color-coded contour lights and in Quantified View, collected data is visualized as infographics. Data Opt-in finally lets users decide whether they would like to share their personal data to enable the affective functionalities described above.…”
Section: Transparency Use Casesmentioning
confidence: 99%
“…Among the problems, emotion-aware human-vehicle interactions are urgently needed to be addressed for improvement [5]. Driver's emotion recognition and regulation are the main topics for emotion-aware human-vehicle interactions [6]. Previous studies have shown that emotion recognition and regulation systems can be used to understand and regulate the emotional state of the driver to enhance the safety, comfort, and acceptance of driving [6], [7].…”
Section: Introductionmentioning
confidence: 99%